INITIAL AND LONG-TERM DISSOLUTION RATES OF ALUMINOSILICATE GLASSES ENRICHED WITH TI, ZR AND ND - Leturcq G.; Berger G.; Advocat T.; Vernaz E. (My University, 1999)
The alteration mechanism and rate of three aluminosilicate glasses were investigated experimentally in aqueous media between 90 and 200°C. In order to assess their containment properties with regard to minor actinides for the purpose of developing new radionuclide containment matrices, the three glasses were enriched with neodymium to simulate the trivalent actinides. The proportions of the major glass network formers, silicon and aluminum, were comparable to those found in tholeitic basalt glasses. The composition differences for the other elements (Ca, Zr, Ti, Nd) revealed the role of glass network modifiers in aqueous corrosion resistance of silicate glasses. Two types of experiments were performed: open-system leaching to determine the dissolution rate constants at 90, 150 and 200°C; and closed-system tests at high (200 cm-1) SA/V ratios (glass-surface-area-to-leaching-solution-volume) for 3 months at 90°C to simulate long-term behavior. The open-system test results showed that, regardless of the aluminosilicate glass composition (not only the test glasses, but also tholeitic basalt glasses and nuclear aluminoborosilicate glasses), the initial dissolution rates are on the same order of magnitude in neutral or slightly basic media, with a common activation energy of 60+/-5 kJ mol-1. This step appears to be controlled exclusively by hydrolysis of the Si-O and/or Al-O bonds, irrespective of the nature of the network modifying or intermediate components. Otherwise, with renewal of the leaching solution, the formation of alteration films at the `glass/solution' interface appears to limit glass alteration; however, the protective effect of these layers depends on the experimental conditions and on the glass composition. Finally, in closed-system conditions studied at 90°C, the three test glasses exhibit very low alteration rates (three to four orders of magnitude lower than the initial rates) without the development of a thick and abundant altered layer. Two hypotheses are discussed to account for these low rates: a protective aluminosilicate surface gel less than 50 nm thick and thus with a low silicon diffusion coefficient (~10-13 cm2 s-1); and a chemical affinity effect with respect to the glass itself, as the solubility products attributed to glass are determined from the thermodynamic model proposed by Paul (1977) [Paul, A., 1977. Chemical durability of glasses: a thermodynamic approach. J. Mater. Sci. 12, 2246-2268.].
Keywords: SPHENE GLASS; ZIRCONOLITE GLASS; SIALON GLASS; BASALTIC GLASS; DISSOLUTION KINETICS; REACTION AFFINITY